Essentials of project proposal writing in librarianship (2015)
This paper focuses on the essentials of project proposal writing in librarianship. Librarianship is basically service-oriented and mostly non-for-profit. Their needs are enormous as they thrive to provide Services to their teeming users with the limited resources available to them. In doing this, they approach funding organizations, foundations and government agencies for support. As there are many contending libraries and organizations competing for scarce grants, the skills in writing project proposals become very important when sourcing for support to execute library projects. The paper discusses projects and the development of library and Information Services; the general guidelines for proposal writing: the structure and contents of project proposals; project details and descriptions; the budget contents and; the organizational Information. In all these, attention is drawn to the salient ingredients that make project proposals attractive to potential funding organizations